An exploration study of effectiveness of child parent relationship therapy (CPRT) on children internalizing behavior problems - Alizadeh, Shahla; Abu Talib, Mansor; Abdullah, Rohani; Mansor, Mariani (American-Eurasian Network for Scientific Information, 2011)
The application of positive parenting training for mothers and fathers which affects family members has received little attention and research interest in Iran. Therefore the current research is necessary. More than ever, the family today has a significant role to play in their children’s development. The major purpose of this current study is to determine the effect of child-parent relationship therapy (CPRT) on children’s internalizing symptoms (anxiety, fearfulness, depression and withdrawal). The study is an experimental research among mothers of children in primary school with internalizing behavioral problems in Tehran, Iran. Respondents comprised of 43 mothers in the experimental group and 43 other mothers in the control group who were randomly assigned. A CPRT as a training program was conducted with the experimental group over ten sessions lasting a total of two months. Instruments for data collection included the Children’s Behavior Checklist (CBCL) and one intervention in the form of CPRT, applied in the experimental stage. The results of the present study indicated that there is a significant difference in the internalizing symptoms between pre- and post-tests in the experimental group. They also demonstrated that CPRT as a treatment in the experimental group was effective and led to a significant change in maternal perspective as reflected by a decrease in the internalizing behavior problems of children [F (1, 42) = 85.62, p<.01, ηp2= .67, F=.9]. In conclusion, the mothers in this program learned reflective listening, recognizing and responding to children’s feelings, all of which in turn improved their children’s behaviour.